Pengaruh Faktor Dukungan Keluarga, Faktor Dukungan Sosial Dan Faktor Dukungan Lingkungan Terhadap Stress Pada Mahasiswa Tingkat Akhir - saputri, liana; martani, rahajeng win; rusdi, rusdi (PENA NURSING, 2024)
Stress is a physical and emotional reaction that arises whes someone experiences pressure, worry or difficulty in dealing with certain situations. Students who experience stress when working on their final project or thesis can have an impact on changing sleep patterns, decreased appetite and so on. However, the attention and support from the closest person can increase the enthusiasm in doing the final project again. The purpose of this study was conducted to determine the factors that cause stress in final year students in doing their final project. This research is a quatitative study that uses a correlation analysis method with a cross sectional research design. The results of the research conducted are variable Y and X₁ 0,044<0.05 is there a significant influence. Variable Y with X₂ 0,220>0,05 is that there is no significant effect, variable Y with X₃ 0,006<0,05 is that there is a significant efeect. The pearson correlation value on variable X₁has a value of -0,191, variable X₂ has value of =0,117 and variable X₃ has a pearson correlation value of -0,257. The pearson correlation value on variables X₁,₂,₃and variable Y is negative, wich means that the pearson correlation value is  unidirectional.Keyword : stress, students, final project.